Analisis Persepsi Kemampuan Transferable Skills Guru Sekolah Menengah Kejuruan Program Keahlian Ganda Ditinjau Dari Usia dan Jenis Bidang Keahlian - Purnomo Purnomo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: This research aimed (1) to determine the relationship of age and the perception towards transferable skill of Vocational High School teachers from the On-In-On-In Double-expertise Program for teachers in Malang; (2) to determine the relationship between types of expertise  the perception towards transferable skill of Vocational High School teachers from the On-In-On-In Double-expertise Program for teachers in Malang; (3) to find out the significant interaction between the fields of expertise and age on the perceptions of the transferable skills of Vocational High School On-In-On-In Dual Vocational Skills in Malang. Respondents consist of 97 teachers from 14 Vocational Schools in Malang selected by simple random sampling. This study used a quantitative descriptive approach. The results showed the following (1) there is a significant relationship between of age and the perceptions of transferable skills of teachers; (2) there is a relationship between types of expertise with perceptions of teacher transferable skills; (3) there was a significant interaction between fields of expertise with age on perceptions of teacher transferable skills.Abstrak: Penelitian ini bertujuan (1) untuk mengetahui hubungan usia dengan persepsi kemampuan transferable skills guru Sekolah Menengah Kejuruan Program Keahlian Ganda On-In-On-In di Kota Malang, (2) untuk mengetahui hubungan jenis bidang keahlian dengan persepsi kemampuan transferable skills guru Sekolah Menengah Kejuruan Program Keahlian Ganda On-In-On-In di Kota Malang, (3) untuk mengetahui interaksi yang signifikan antara bidang keahlian dan usia terhadap persepsi kemampuan transferable skills guru Sekolah Menengah Kejuruan Program Keahlian Ganda On-In-On-In di Kota Malang. Responden berjumlah 97 guru, yang berasal dari 14 SMK di kota malang diambil secara simple random sampling. Penelitian ini menggunakan pendekatan deskriptif kuantitatif. Hasil penelitian diperoleh (1) terdapat hubungan yang signifikan usia dengan persepsi kemampuan transferable skills guru; (2) terdapat hubungan yang jenis bidang keahlian dengan persepsi kemampuan transferable skills guru; (3) terdapat interaksi yang signifikan antara bidang keahlian dan usia terhadap persepsi kemampuan transferable skills guru.